Relationship between resting state alpha electroencephalographic rhythms and aging in cognitively unimpaired seniors and patients with mild cognitive impairment due to Alzheimer's disease and amnestic mild cognitive impairment. (31st December 2021) - Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Güntekin, Bahar; Yener, Gorsev; Marizzoni, Moira; Frisoni, Giovanni B; Babiloni, Claudio
Abstract: Background: The rsEEG alpha rhythms reflect cortical neural synchronization mechanisms underpinning the inhibition of sensory, cognitive, and motor areas in parietal, temporal, and occipital cortex during a condition of low vigilance. Here we tested the hypothesis that age may diversely affect rsEEG alpha (8‐12 Hz) rhythms recorded in normal elderly (Nold) seniors and patients with Alzheimer's disease and mild cognitive impairment (ADMCI). Method: Clinical and rsEEG datasets in 63 ADMCI and 60 Nold individuals ‐ matched as demography, education, and gender ‐ were taken from an international archive. The rsEEG rhythms were investigated at individual delta, theta, and alpha frequency bands as well as fixed beta (14‐30 Hz) and gamma (30‐40 Hz) bands. Each group was stratified into three subgroups based on age ranges (i.e., tertiles). Result: As compared to the younger Nold subgroups, the older one showed greater reductions in the rsEEG alpha rhythms with major topographical effects in posterior regions (Figure 1 top). On the contrary, in relation to the younger ADMCI subgroups, the older one displayed lesser reduction in those rhythms (Figure 1 bottom). Notably, the ADMCI subgroups pointed to similar cerebrospinal fluid AD diagnostic biomarkers, gray and white matter brain lesions as revealed by neuroimaging, and clinical and neuropsychological scores. Conclusion: The present results suggest that age may represent a deranging factor for dominant rsEEG alpha rhythms in Nold seniors, while rsEEG alpha rhythms in ADMCI patients may be more affected by the disease variants related to earlier vs. later onset of the AD.